2020
DOI: 10.1186/s13023-020-1301-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of liver MRI R2(FerriScan®) VS liver MRI T2* as a measure of body iron load in a cohort of beta thalassaemia major patients

Abstract: To compare the similarity of the non-patented T2* and the high cost patented R2 (Ferriscan®) MRI techniques in the measurement of liver iron concentration (LIC) in heavily transfused patients with thalassaemia major in a reallife Sri Lankan hospital setup. We compared LIC measured by MRI, obtained 2 weeks apart, using both T2* and R2 techniques in 15 patients with beta thalassaemia major. They all had a history of > 100 units of blood transfusions life long and also a history of sub optimal chelation. MRI R2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, by using advanced acquisition protocols (IDEAL method), MRI‐based R2 * mapping enabled reliable and reproducible measurement for predicting hepatic iron content (HIC) 14,15 . R2 * was reported to be strongly correlated with histological iron grades/HIC acquired by liver biopsy and R2‐based method which was approved by the Food and Drug Administration for the measurement of HIC (FerriScan®) 11,15–17 . However, another previous report suggested that R2 * was not useful for quantifying hepatic iron accumulation in NAFLD patients because of the influence of fat deposition 18 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, by using advanced acquisition protocols (IDEAL method), MRI‐based R2 * mapping enabled reliable and reproducible measurement for predicting hepatic iron content (HIC) 14,15 . R2 * was reported to be strongly correlated with histological iron grades/HIC acquired by liver biopsy and R2‐based method which was approved by the Food and Drug Administration for the measurement of HIC (FerriScan®) 11,15–17 . However, another previous report suggested that R2 * was not useful for quantifying hepatic iron accumulation in NAFLD patients because of the influence of fat deposition 18 .…”
mentioning
confidence: 99%
“…14,15 R2 * was reported to be strongly correlated with histological iron grades/HIC acquired by liver biopsy and R2-based method which was approved by the Food and Drug Administration for the measurement of HIC (FerriScan ® ). 11,[15][16][17] However, another previous report suggested that R2 * was not useful for quantifying hepatic iron accumulation in NAFLD patients because of the influence of fat deposition. 18 Therefore, R2 * usefulness in evaluating HIC in NAFLD patients is controversial.…”
mentioning
confidence: 99%
“…The use of magnetic resonance imaging (MRI) techniques involving transverse relaxation times such as the T2 and T2* have shown promising results in estimating iron concentration in transfusion-dependent patients 8 , 9 . It is therefore, expected that the serum ferritin and invasive biopsy methods will be replaced by the MRI methods, however, there is limited data in the literature that systematically compared T2 and T2* sequences in sickle cell anemia (SCA) 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The LIC F reported by FerriScan (Resonance Health Limited, Burswood, WA, Australia) based on MRI T2/R2 (1000/T2) images has been certi ed by the US Food and Drug Administration (FDA) and has high reliability [3,4]. But this technique also has many limitations [5]: this technique requires sending the patient's MRI data to FerriScan for remote post-processing and analysis. Sending patients data to other places requires the approval of relevant institutions, and the time cost prolongs the time to obtain LIC results.…”
Section: Introductionmentioning
confidence: 99%